The Relationship between oganizational climate and job satisfaction: a study on production operators of a car manufacturing company in Malaysia - June M.L. Poon; Raja Azimah R.O. Ainuddin (Penerbit Universiti Kebangsaan Malaysia, 1989)
The purpose of this stdy was to examine the relationshIp between perceived organizational climate and job satisfaction. Data were obtained from 346 productIon operators of a car manufacturing company. Factor analyses of climate items yielded 10 climate dimensions. CorreiatiOn results showed significant relationships between the derived climate dimensions and measures of job satisfaction.